Characterization of Lignin Peroxidase from the Suspected Novel Strain Phanerochaete chrysosporium ITB Isolate - Evi Susanti; Tri Ardyati; Suharjono Suharjono; Aulanni'am Aulanni'am (Universitas Gadjah Mada, 2022)
This study was aimed to characterize lignin peroxidase (LiP) obtained from Phanerochaete chrysosporium ITB isolate. The characterizations included molecular weight, the pH and optimum working temperature of the crude extract of the enzyme, the temperature stability, the effect of metal ions and inhibitors, their precipitation with ethanol, and the storage stability. The LiP of P. chrysosporium ITB isolates was 34 kDa. The crude extract of LiP displays high activity at pH between 3 until 5 and 26–32 °C, has good thermal stability at 26–32 °C for 20 h. The activity is affected by Pb2+, K+, Co2+, Fe2+, Cd2+, Mg2+, and Cu2+ EDTA, Na+, Cr3+, Hg2+, NaN3, Ni2+, and Ca2+ ions, is not affected by Mn2+ and Zn2+ ions, precipitated with the optimum ethanol at 64% ethanol saturation which results in an increase in specific activity of 2.3 times. The crude extract storage at 0 °C is more stable than the precipitate resulting from ethanol precipitation and resuspension from ethanol precipitation. These results strengthen that LiP from P. chrysosporium is another LiP isoenzyme that can be used for bioremediation processes. Unfortunately, the concentration using the ethanol precipitation method has not been effective, so further studies using other methods should be required.